Pediatric drug allergy: a retrospective analysis of clinical features, laboratory parameters, and systemic inflammation indices - Şahin, Filiz Demir; Kapçay, Ozan; Kılıç, Mehmet (Codon Publications, 2026)
Background: This study aimed to investigate the potential utility of hematological parameters and systemic inflammatory indices as predictive biomarkers in pediatric patients with drug hypersensitivity reactions (DHRs). Methods: We performed a retrospective review of medical records of children presenting to the Pediatric Allergy and Immunology Clinic at Fırat University Hospital, Turkey, between January 2019 and July 2025 with suspected DHRs. Demographic characteristics, clinical manifestations, reaction phenotypes, complete blood counts, and total immunoglobulin E (IgE) levels were analyzed. Inflammatory indices, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), eosinophil-to-lymphocyte ratio (ELR), and systemic immune–inflammation index (SII), were calculated subsequently. Results: Among the 45 children included, drug allergy was confirmed in 14 (31.1%) children. Total IgE levels did not differ significantly between groups (P = 0.712). Monocyte counts were significantly higher in the patient group (P = 0.039), whereas eosinophil counts were elevated in the control group (P = 0.026). Lymphocyte (P = 0.002) and basophil counts (P = 0.002) were significantly lower in the patient cohort. No significant differences were observed in neutrophil or platelet counts. Regarding inflammatory indices, NLR (P = 0.007), PLR (P = 0.006), and SII (P = 0.007) were significantly increased in the patient group, whereas ELR did not differ significantly (P = 0.073). Conclusion: In this small, single-center cohort (n = 45; confirmed DHR, n = 14), higher NLR, PLR, and SII were observed among children with confirmed DHRs. These preliminary findings suggest that readily available hematological indices may aid hypothesis generation and tentative risk stratification; however, they should be interpreted cautiously and require confirmation in larger prospective studies. © 2026 Codon Publications.
Keywords: Drug Hypersensitivity Reactions; Inflammatory Biomarkers; Pediatric Drug Allergy